Between Philosophy and Sophistry: the case of Dio of Prusa (1st and 2nd Centuries) - Erlacher, Esdra (Romanitas - Revista de Estudos Grecolatinos, 2026)
Abstract: The textual, epigraphic, and material sources of the Roman Empire reveal to us that it was common, in the context of the Principate, to find sophists, philosophers, and rhetors circulating through the poleis and civitates. Although we know that philosophy and sophistry were distinct domains of knowledge, with their own teachers and educational centers, in practice, their boundaries often became fluid, so that the same individual could simultaneously play the role of both sophist and philosopher. An exemplary case is that of Dio of Prusa, who has been classified since Antiquity sometimes as a sophist, sometimes as a philosopher. Considering the different identities attributed to the author, our objective in this article is to discuss, based on Dio’s speeches, how sophistry and philosophy were addressed in his discourses and how the orator himself wished to be recognized.